Influence of ADAM metallopeptidase with thrombospondin type 1 motif 9 on the prognosis of patients with thyroid cancer and its mechanism of action - CAO Xiaodong, XIANG Cheng (精准医学杂志)
Objective To investigate the influence of ADAM metallopeptidase with thrombospondin type 1 motif 9 (ADAMTS9) on the prognosis of patients with thyroid cancer (THCA) and its potential mechanism of action. Methods TCGA database was used to obtain the data on the expression level of ADAMTS9 in THCA tissue and the clinical data of patients, and HPA database was used to obtain the data on the protein expression level of ADAMTS9 in THCA tissue. The expression level of ADAMTS9 was compared between normal tissue and THCA tissue, as well as the degree and intensity of ADAMTS9 protein staining. A functional enrichment analysis was used to predict the biological processes involving ADAMTS9 in THCA. The Kaplan-Meier Plotter database was used to analyze the influence of the expression level of ADAMTS9 on the overall survival time of THCA patients, and gene set enrichment analyses were used to explore the potential signaling pathways associated with ADAMTS9 and important prognostic factors in THCA. Results Compared with normal tissue, THCA tissue showed a significantly higher expression level of ADAMTS9 (t=12.35,P<0.05) and significantly higher degree and intensity of ADAMTS9 protein staining (t=18.68,12.35,P<0.05). The functional enrichment analysis showed that ADAMTS9 mainly participated in the regulation of RNA slicing and gene expression. The patients with high ADAMTS9 expression had a significantly longer overall survival time than those with low expression (HR=0.22,95%CI=0.06-0.76,P<0.05). The pathway analysis showed that the expression level of ADAMTS9 was positively correlated with calcium signaling pathway score (NES=1.852,P<0.05) and was negatively correlated with glycosphingolipid biosynthesis pathway score and citrate cycle pathway score (NES=-1.581,-1.863,P<0.05). Age (HR=1.11,95%CI=1.05-1.67,P<0.05) was an independent prognostic factor for the overall survival time of patients, and significant enrichment of energy metabolism-related pathways was observed in elderly THCA patients, such as citrate cycle and fatty acid metabolism. Conclusion High mRNA and protein expression levels of ADAMTS9 are observed in THCA tissue, which is favorable to the prognosis of patients, possibly by inhibiting energy-related pathways. In addition, the effect of ADAMTS9 might offset the adverse effect of age on prognosis to a certain degree.